Difference in outcomes following allogeneic hematopoietic cell transplantation for patients with acute myeloid leukemia and myelodysplastic syndromes. Issue 14 (6th December 2021) - Yanada, Masamitsu; Mizuno, Shohei; Yamasaki, Satoshi; Harada, Kaito; Konuma, Takaaki; Tamaki, Hiroya; Shingai, Naoki; Uchida, Naoyuki; Ozawa, Yukiyasu; Tanaka, Masatsugu; Onizuka, Makoto; Sawa, Masashi; et al.
Abstract: To evaluate whether outcomes following allogeneic hematopoietic cell transplantation differ according to disease type, a three-way comparison for patients with de novo acute myeloid leukemia (AML) ( n  = 3318), AML evolving from myelodysplastic syndromes (MDS) ( n  = 208), and MDS with excess blasts (MDS-EB) ( n  = 994) was performed. The 5-year probabilities of overall survival (OS) for de novo AML, AML evolving from MDS, and MDS-EB were 60%, 42%, and 41% ( p  < 0.001), respectively. Multivariate analysis revealed that, compared to de novo AML, AML evolving from MDS was associated with a higher risk of NRM ( p  = 0.030) and MDS-EB with a higher risk of relapse ( p  < 0.001), both leading to lower OS ( p  = 0.010 and p  < 0.001, respectively). These findings demonstrate inter-disease differences in post-transplant outcomes and highlight the needs to reduce NRM for AML evolving from MDS and to reduce relapse for MDS-EB.